Kalsium Silikat sebagai Bahan Komposit Biosemen Gigi dengan Penyiapan Silika dari Sekam Padi melalui Metode Sol-Gel - Haryono MT; Diana Rakhmawaty Eddy; Atiek Rostika Noviyanti; Solihudin Solihudin; Laelaturrohmah Laelaturrohmah (Jurnal Kartika Kimia, 2018)
Rice husk has the content of organic and inorganic compounds that have not been utilized maximally, one of them is silica. High silica content in rice husks can be used as an alternative source of potential silica for the synthesis of calcium silicate as a base material of Trioxide Aggregate mineral composites in tooth biocement. In this study, calcium silicate was obtained through two stages of the process, namely silica isolation from rice husk ash by sol-gel method, and reacting between silica and calcium oxide. Silica and calcium oxide are reacted to the mole ratio between silica to calcium oxide of 7:3, 6:4, 4:6, and 3:7. The isolated silica is characterized by the distribution of the size and composition of each element with Particle Size Analyzer (PSA) and EDS. The formation of calcium silicate and its size distribution from the synthesis stage is determined by XRD and PSA. The result showed that silica isolation from rice husk ash with sol-gel method obtained silica with content and particle size of 71.6% and 52.82 mm. While the optimum condition of calcium silicate synthesis was achieved at the mole ratio of silica to calcium oxide by 4:6. In the mole ratios obtained calcium silicate type b-dicalcium silicate with an average particle size of 102.2 mm.